A solid waste-based core-shell hollow sphere filler made of bamboo pottery and a preparation method and application thereof
Patent Information
- Application Number
- CN202511537582.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-10-27
AI Technical Summary
然而,现有污水处理技术仍存在显著局限性:在活性污泥工艺中,抗生素会对反硝化菌和聚磷菌等重要功能微生物产生明显抑制,导致系统脱氮效率下降可达40-50%,除磷稳定性亦大幅减弱,难以实现深度处理目标;普通陶粒滤池所使用的填料多呈均质结构,缺乏可与抗生素分子结合的特异性吸附位点(如氨基、羟基等官能团),在实际应用中抗生素平均去除率普遍低于60%,无法稳定达到《城镇污水处理厂污染物排放标准》(GB18918-2002)中对特征污染物的限值要求
(1)本发明以竹基和陶基固体废弃物为主要原料,通过由外至内“壳-核-中空”三级结构设计,实现抗生素高效吸附与深度脱氮的协同处理:内核竹基多孔碳-陶基烧结复合层通过物理与化学吸附富集抗生素,减轻对微生物抑制;外壳陶基微孔为底物传输提供通道;中空腔体内维持缺氧环境,促进反硝化菌增殖与抗生素降解,从而实现“吸附-降解-脱氮”一体协同,避免吸附饱和。
Smart Images

Figure CN121158956B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the interdisciplinary field of environmental functional materials and wastewater treatment, specifically to a bamboo-ceramic solid waste-based core-shell hollow spherical packing material, its preparation method, and its application. Background Technology
[0002] With the large-scale development of the pharmaceutical, medical, and aquaculture industries, the annual discharge of industrial and agricultural wastewater containing sulfonamides, tetracyclines, and quinolones has continued to increase. It is estimated that this type of wastewater has become a major source of antibiotic residues in surface water bodies, with antibiotic concentrations reaching hundreds to thousands of micrograms per liter in some areas of industrial discharge outlets. Antibiotics have stable molecular structures and strong biotoxicity, not only easily remaining in water bodies for extended periods (with half-lives exceeding 100 days), but also inducing the spread of drug-resistant bacteria and resistance genes, posing a serious threat to the ecological environment and public health. However, existing wastewater treatment technologies still have significant limitations: in activated sludge processes, antibiotics significantly inhibit important functional microorganisms such as denitrifying bacteria and polyphosphate-accumulating bacteria, leading to a 40-50% decrease in system denitrification efficiency and a substantial reduction in phosphorus removal stability, making it difficult to achieve deep treatment targets; the packing materials used in ordinary ceramsite filters are mostly homogeneous in structure, lacking specific adsorption sites (such as amino and hydroxyl functional groups) that can bind to antibiotic molecules. In practical applications, the average antibiotic removal rate is generally below 60%, failing to consistently meet the limits for characteristic pollutants in the "Discharge Standard of Pollutants for Municipal Wastewater Treatment Plants" (GB18918-2002). Therefore, developing treatment technologies that combine high adsorption performance with good biocompatibility has become an urgent need for the industry.
[0003] my country generates over ten million tons of bamboo-based solid waste (such as bamboo processing waste and bamboo fiber residue) and ceramic-based solid waste (such as ceramic scraps and waste building ceramic powder) annually, with over 80% currently disposed of through landfill or open-air incineration. Landfilling not only occupies vast amounts of land resources but also poses risks of heavy metal accumulation in soil and groundwater pollution; incineration easily releases carbonaceous particulate matter and volatile organic compounds, causing significant secondary air pollution. Although some studies have attempted to use this type of solid waste in the preparation of water treatment fillers, due to a lack of systematic structural and functional design, fillers prepared simply through crushing and mixing typically have a specific surface area of less than 50 m². 2 With a compressive strength of less than 1.5 MPa, it is difficult to achieve efficient synergy in "adsorption-biodegradation-mass transfer". In addition, existing hollow or core-shell structure packings still have obvious shortcomings: for example, some patented technologies use raw materials such as resin, artificial clay or polyvinyl alcohol, which fail to fully realize the resource utilization of solid waste. Their structural stability and functional synergy are also not ideal. They are prone to swelling or damage under complex water quality conditions, and their functions have not been optimized for antibiotic adsorption, making it difficult to cope with the water quality fluctuations and treatment requirements of actual wastewater.
[0004] Currently, the treatment of antibiotic-containing wastewater faces three prominent contradictions: the contradiction between wastewater treatment effectiveness and stringent discharge standards, with antibiotic removal rates in typical systems significantly falling short of standard requirements; the contradiction between environmentally friendly solid waste disposal and resource utilization rates, with a large amount of solid waste still not achieving high-value reuse; and the contradiction between the techno-economic efficiency and functional integrity of packing materials, as traditional packing materials struggle to simultaneously meet requirements for mechanical strength, adsorption capacity, and biocompatibility. These contradictions collectively lead the industry into a vicious cycle of "difficulty in meeting treatment standards, high operating load, and severe secondary pollution." Continuing with existing technological approaches will also generate a considerable amount of secondary pollutants per unit volume of wastewater treated. Therefore, developing novel packing materials and their application methods that utilize all solid waste as raw materials, employ a multi-stage structural design including a "high-adsorption core, high-strength shell, and hollow mass transfer chamber," and integrate intelligent operation strategies for dynamic water quality control, can achieve large-scale resource utilization of solid waste while effectively improving antibiotic removal performance, thus overcoming existing technological bottlenecks. This direction combines significant technological innovation with industrial application value, and is expected to drive the industry towards "solid waste resource utilization, efficient treatment, and low-carbon operation", providing a new path for the treatment of antibiotic-containing wastewater that balances environmental protection and economic efficiency. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a bamboo-ceramic solid waste-based core-shell hollow spherical filler, its preparation method, and its application.
[0006] The technical solution of the present invention is: a bamboo-ceramic solid waste-based core-shell hollow spherical filler, wherein the filler is a spherical particle with a particle size of 3-8mm, and has a three-level composite structure of "shell-core-hollow" from the outside to the inside; wherein, the core is a hydrophilic bamboo-based porous carbon-ceramic sintered composite layer, the outer shell is a ceramic sintered layer, and the middle is a cavity; Explanation: Core: Composed of high specific surface area bamboo-based porous carbon formed by pyrolysis carbonization and hydrophilic modification of bamboo-based solid waste. Its function is to efficiently enrich antibiotic molecules in water through physical adsorption and distribution. At the same time, its rough and porous hydrophilic surface provides abundant attachment sites for functional microorganisms (such as denitrifying bacteria and antibiotic degrading bacteria). The outer shell is composed of a dense ceramic layer formed by wrapping and sintering ceramic-based solid waste slurry. Its function is to provide the necessary mechanical strength for the entire packing material and prevent the loss of the internal porous carbon core. Its inherent microporous structure provides an efficient mass transfer channel for substrates, nutrients and metabolites. Hollow cavity: formed by high-temperature sintering and volatilization of granulation template. Its function is to be an oxygen-deficient "microreactor" at the core. The physical barrier of the outer shell can effectively block the rapid diffusion of dissolved oxygen from the outside, thereby maintaining a stable oxygen-deficient microenvironment inside the cavity, specifically enriching denitrifying bacteria and promoting the oxygen-deficient biodegradation of specific antibiotics.
[0007] The present invention provides a method for preparing a bamboo-ceramic solid waste-based core-shell hollow spherical filler, comprising the following steps: S1, Raw Material Processing Prepare bamboo-based solid waste and ceramic-based solid waste separately. Clean and remove impurities from the bamboo-based solid waste, dry it, and then pulverize it through a 100-200 mesh sieve to obtain bamboo-based powder. Clean and remove impurities from the ceramic-based solid waste, dry it, and then pulverize it through a 100-200 mesh sieve to obtain ceramic-based powder. Then, the bamboo-based powder is carbonized under an inert atmosphere to obtain bamboo charcoal powder. The bamboo charcoal powder is then soaked in a 4-5% H2O2 solution and stirred at 22-25℃ for 2-2.5 hours. After drying, hydrophilic bamboo charcoal powder is obtained. Ceramic base powder, binder and dispersant are mixed with water in a mass ratio of 100:5-10:3-5:40-60 and ball-milled to prepare a ceramic slurry with a viscosity of 500-800 mPa·s. S2, Preparation of core-shell structured raw material pellets Using volatile organic compound spheres as templates, a small amount of ceramic slurry is first sprayed onto the template surface to moisten the surface of the volatile organic compound spheres. Then, hydrophilic bamboo charcoal powder is coated onto them. This process is repeated alternately with spraying a small amount of ceramic slurry and coating with hydrophilic bamboo charcoal powder to ensure effective adhesion of the hydrophilic bamboo charcoal powder. After each coating, the spheres are rolled and granulated to obtain a core with a hydrophilic bamboo-based porous carbon layer as the outermost layer. A layer of ceramic slurry is then sprayed onto the outermost layer, and the rolling and granulation process continues to obtain a ceramic-based sintered outer shell, forming raw material spheres with a core-shell structure and a particle size of 3-8 mm. Qualified raw material spheres must meet the condition of "not breaking when dropped from a height of 1 m without any slurry dripping". Additional explanation: Naphthalene balls are used as a new granulation mold. First, a small amount of ceramic slurry is sprayed on to make it moist and viscous. Then, bamboo charcoal powder is coated onto this slurry to form the innermost layer. Next, ceramic slurry is sprayed onto the existing bamboo charcoal powder layer, and this process of "coating bamboo charcoal powder and spraying ceramic slurry" is repeated continuously until the appropriate sphere size is achieved. This ensures that the outermost layer of the raw material sphere is always a ceramic slurry layer. Therefore, after calcination, the middle layer volatilizes to form a cavity, the bamboo charcoal powder solidifies, and the outer layer is a ceramic layer formed by the ceramic slurry. From the outside to the inside, we see the following sequence: shell (ceramic) → core (bamboo charcoal-ceramic) → hollow (cavity). However, here we are referring to the functional description: a synergistic system protected by an outer shell, containing an adsorption / biological core and an oxygen-deficient micro-reaction cavity. S3, Post-processing The raw material balls with a core-shell structure are dried by forced air at 60-105℃ for 4-12 hours until the moisture content is <5%. Then, under nitrogen atmosphere protection, the temperature is raised to 1050-1150℃ at a heating rate of 2-5℃ / min and held for 0.5-2 hours to obtain the core-shell hollow spherical filler based on bamboo ceramic solid waste. The filler with a particle size of 3-8mm is screened and sealed in packaging.
[0008] Explanation: Low-concentration H2O2 solution was used to hydrophilically modify bamboo charcoal. The mechanism of action is to introduce oxygen-containing functional groups such as carboxyl groups (-COOH) and hydroxyl groups (-OH) on the surface of carbon materials through mild oxidation, which significantly improves the surface hydrophilicity. This not only greatly promotes the interfacial bonding strength with inorganic ceramic slurry in the subsequent granulation process, but more importantly, it creates favorable conditions for the microbial adhesion and biofilm formation process in the initial stage of start-up, overcoming the drawback of poor biocompatibility of traditional hydrophobic carbon materials.
[0009] Furthermore, the bamboo-based solid waste is bamboo shavings or bamboo powder, and the ceramic-based solid waste is waste clay or waste porcelain powder; Note: Bamboo-based solid waste uses bamboo chips or bamboo powder. Their advantages are: after carbonization, bamboo chips and powder easily form a porous structure with a high specific surface area (measured specific surface area 350 m² / g), which can efficiently adsorb antibiotics. Furthermore, their surface is easily modified by H₂O₂ to introduce oxygen-containing functional groups, facilitating microbial biofilm formation. Simultaneously, both are common solid wastes from bamboo processing, resulting in low resource recovery costs and no secondary pollution. If wood chips or straw are used instead, the specific surface area after carbonization is low (<200 m² / g), reducing antibiotic adsorption capacity by more than 40% and extending the biofilm formation period to 8-10 days. Replacing them with plastic waste, etc., lacks a porous structure and cannot provide a basis for microbial attachment, directly leading to the failure of the core function. Ceramic-based solid waste uses waste clay or waste porcelain powder. Its advantages are: after sintering, it forms a dense microporous structure (porosity 42-45%), possessing both mechanical strength (compressive strength 2.3-2.5 MPa) and mass transfer capacity, preventing core loss and ensuring substrate transport. If ordinary clay is used instead, it is prone to cracking after sintering, with a compressive strength of <1.2MPa, and will break in 3-5 days; if construction waste powder is used instead, it cannot form continuous micropores, mass transfer is blocked, the antibiotic removal rate is less than 20%, and impurities may be dissolved to pollute the wastewater.
[0010] Furthermore, in S1, the inert atmosphere is nitrogen gas with a flow rate of 40-50 mL / min, and the carbonization conditions are: heating to 400-600℃ at a heating rate of 5℃ / min and holding at that temperature for 1-2 hours; Explanation: The advantages of these carbonization conditions are: a slow heating rate of 5℃ / min prevents the collapse of the bamboo-based powder's porous structure due to thermal shock; a temperature range of 400-600℃ effectively removes organic matter from the bamboo powder while preserving its well-developed porous structure, ensuring a high specific surface area (>300m² / g) for the core; a nitrogen atmosphere prevents oxidation of the carbon material; and a flow rate of 40-50mL / min promptly removes volatiles, preventing pore blockage. The advantages for wastewater treatment are: the high specific surface area of the core allows for efficient adsorption of antibiotics, and the porous structure provides ample attachment sites for microorganisms, ensuring synergistic adsorption-degradation, resulting in an antibiotic removal rate ≥90% and a biofilm formation period ≤5 days.
[0011] Furthermore, in S2, the volatile organic compound spheres are naphthalene spheres with a diameter of 1-2 mm. The single spraying time of the ceramic slurry increases accordingly within 13-70 s as the particle size of the raw material spheres increases. During the preparation of the core, the amount of hydrophilic bamboo charcoal powder used per application is 0.2-1.2 g, and the spraying rate of the ceramic slurry is 100-300 μL / s. This satisfies the requirement that when the particle size of the raw material spheres increases to about 3-4 mm, the single spraying time is controlled to be 13-20 s; when the particle size increases to about 5-6 mm, the single spraying time is controlled to be 25-40 s. During the preparation of the outer shell, i.e., when the particle size increases to about 7-8 mm, the spraying rate of the ceramic slurry is 100-300 μL / s, and the single spraying time is controlled to be 50-70 s. Note: By precisely controlling the spraying rate of the ceramic slurry and the amount of carbon powder added, the core-shell thickness and ratio can be accurately controlled. Furthermore, the naphthalene balls can be completely volatilized without leaving any residue during the subsequent high-temperature sintering stage, thus forming a hollow cavity with a regular structure and smooth inner wall, which is crucial for maintaining a stable internal microenvironment.
[0012] Furthermore, the binder is starch, and the dispersant is sodium carboxymethyl cellulose; Note: Starch is chosen as the binder because it is a natural organic compound that completely decomposes after sintering without leaving any residue, thus not affecting wastewater quality. It also enhances the interfacial bonding between the ceramic slurry and bamboo charcoal powder, ensuring the mechanical strength of the raw material balls. Sodium carboxymethyl cellulose (CMC) is chosen as the dispersant to ensure uniform dispersion of the ceramic base powder in the slurry, preventing sedimentation and maintaining a stable viscosity of 500-800 mPa·s, guaranteeing the density of the outer shell. If a synthetic binder (such as polyvinyl alcohol) is used instead, toxic substances may remain after sintering, polluting the wastewater. If other dispersants (such as polyethylene glycol) are used, the slurry is prone to stratification, resulting in uneven shell thickness and a decrease in mechanical strength of over 30%.
[0013] This invention also provides an application of bamboo-ceramic solid waste-based core-shell hollow spherical packing material, which is used to treat antibiotic-containing wastewater in anoxic biological filters. Configuration of anoxic biological filter: Construct an upflow or downflow anoxic biological filter with a total filling height of 1.5-2.0m and a filling rate of 60-70%; the filling material consists of bamboo-ceramic solid waste-based core-shell hollow spheres with a particle size of 2-6mm and an effective specific surface area of 500-600m². 2 / m 3 The ordinary ceramsite is composed of a compound with a volume ratio of 5-20:80-95; When applying the solution, start the anoxic biological filter, inoculate it with activated sludge or compound denitrifying bacteria from the anoxic section of the pharmaceutical wastewater treatment plant, aerate for 24 hours, then add glucose at a mass concentration of 50 mg / L as a co-metabolic carbon source, and gradually increase the influent flow rate to the target value within 12 hours. During operation, control the dissolved oxygen in the anoxic biological filter to be 0.2-0.5 mg / L and the pH to be 7.0-8.0. Explanation: Benefits of adding ordinary expanded clay aggregate: Ordinary expanded clay aggregate is low in cost, reducing the total cost of the packing material. Its pore structure can adjust the overall porosity of the filter bed, preventing excessive accumulation of bamboo-ceramic packing material and thus avoiding impaired hydraulic flow. Significance of a packing material filling rate of 60-70%: Below 60%, the packing layer has excessively large voids, resulting in strong hydraulic impact and potential biofilm detachment; above 70%, the mass transfer channels are narrow, leading to insufficient contact between the substrate and microorganisms, and a decrease in denitrification efficiency of more than 20%. The dissolved oxygen limit of 0.2-0.5 mg / L: This maintains an anaerobic environment, meeting the activity requirements of denitrifying bacteria. If DO > 0.5 mg / L, it will inhibit denitrifying bacteria, causing the denitrification rate to drop below 50%; if DO < 0.2 mg / L, it will slow down microbial metabolism and reduce antibiotic degradation efficiency. pH 7.0-8.0 limit: This range is the suitable pH for denitrifying bacteria and antibiotic degrading bacteria. If it deviates from the range (such as pH < 6.5 or > 8.5), the microbial activity will decrease by more than 40%, and at the same time, it will affect the binding ability of bamboo charcoal surface functional groups to antibiotics, resulting in a 15-20% reduction in antibiotic removal rate.
[0014] Furthermore, the application is based on two core indicators of influent: "total antibiotic concentration" and "BOD5 / COD," and adopts a tiered operation strategy. The tiered operation method is as follows: When the total antibiotic concentration is ≤100 μg / L and BOD5 / COD ≥0.3, The first-level scheme is activated: the core-shell hollow spherical packing material based on bamboo and ceramic solid waste accounts for 5-10% of the total packing volume, the hydraulic retention time is 4-6 hours, and the denitrification volumetric load is 0.3-0.5 kgN / (m³・d). When the total antibiotic concentration is 100-200 μg / L or BOD5 / COD < 0.3, The secondary scheme is activated: the core-shell hollow spherical packing material based on bamboo ceramic solid waste accounts for 10-15% of the total packing volume, the hydraulic retention time is 6-8h, and the denitrification volumetric load is 0.2-0.4kgN / (m³・d). When the total concentration of antibiotics is >200 μg / L or the wastewater has bioinhibitory properties... The three-stage scheme is implemented: the core-shell hollow spherical packing material based on bamboo and ceramic solid waste accounts for 15-20% of the total packing volume, the hydraulic retention time is 8-10h, and the denitrification volumetric load is 0.1-0.3kgN / (m³・d). The method for determining the biological inhibition is as follows: after the influent sample is mixed with activated sludge for 20-30 minutes, the sludge settling ratio decreases by more than 20%. Explanation: The benefits of using a tiered operation are as follows: Process parameters can be precisely matched according to the influent water quality, avoiding resource waste and substandard treatment; at low loads (primary scheme), the amount of bamboo ceramic filler and HRT can be reduced, lowering operating costs; at medium and high loads (secondary and tertiary schemes), the proportion of bamboo ceramic filler and HRT can be increased, enhancing adsorption and degradation capabilities, resisting high concentrations of antibiotics or bioinhibition shocks, and ensuring stable effluent compliance (e.g., the tertiary scheme can handle antibiotic wastewater >200μg / L with a removal rate ≥92%).
[0015] Furthermore, the ratio of carbon source to filler is dynamically adjusted during operation: If the effluent nitrate nitrogen concentration is >15mg / L, then glucose carbon source should be added, and the dosage should be controlled to increase the influent COD by 50-100mg / L. If the effluent antibiotic concentration is greater than 10% of the influent antibiotic concentration, the proportion of bamboo ceramic filler should be increased by 3%-5%, but the total proportion should not exceed 20%. If the effluent nitrate nitrogen concentration is >15mg / L and the effluent antibiotic concentration is >10% of the influent antibiotic concentration, then adjust the water according to the order of first adding carbon source and then increasing the proportion of packing material.
[0016] Note: Dynamic adjustment can respond in real time to fluctuations in influent water quality or deviations in operating parameters, preventing the system from failing to meet standards for a long time; adding carbon sources can quickly solve the problem of insufficient carbon sources for denitrification and improve nitrogen removal efficiency; increasing the proportion of packing material can enhance antibiotic adsorption capacity and specifically solve the problem of insufficient antibiotic removal; the order of adding carbon sources first and then adding packing material can prioritize the activity of microorganisms, avoid mass transfer obstruction caused by blindly increasing packing material, and ensure that the system stably recovers to meet standards.
[0017] Compared with existing technologies, the beneficial effects of this invention are: (1) This invention uses bamboo-based and ceramic-based solid waste as the main raw materials. Through the three-level structure design of "shell-core-hollow" from the outside to the inside, it realizes the synergistic treatment of efficient adsorption and deep denitrification of antibiotics: the core bamboo-based porous carbon-ceramic sintered composite layer enriches antibiotics through physical and chemical adsorption, reducing the inhibition of microorganisms; the outer shell ceramic micropores provide channels for substrate transport; the hollow cavity maintains an oxygen-deficient environment, promotes the proliferation of denitrifying bacteria and the degradation of antibiotics, thereby realizing the integrated synergy of "adsorption-degradation-denitrification" and avoiding adsorption saturation.
[0018] (2) The present invention also provides a systematic and intelligent application method for the packing material. The system’s shock resistance is enhanced by the “dual core index matching three-level scheme” operation strategy, providing a comprehensive solution for the efficient and low-consumption treatment of antibiotic wastewater. The process parameters can be accurately matched according to the water quality to avoid resource waste and substandard treatment. The amount of bamboo ceramic packing material and HRT are reduced during low load (first-level scheme) to reduce operating costs. During medium and high load (second-level and third-level schemes), the proportion of bamboo ceramic packing material and HRT are increased to enhance adsorption and degradation capabilities, resist high concentrations of antibiotics or biological inhibitory shocks, and ensure stable effluent compliance. Attached Figure Description
[0019] Figure 1 This is a process flow diagram of the application of this invention; In the attached diagram, "bamboo ceramic filler" refers to "bamboo ceramic solid waste-based core-shell hollow sphere filler". Detailed Implementation
[0020] To further illustrate the methods and effects of this invention, the technical solution of this invention will be clearly and completely described below in conjunction with experiments.
[0021] Example 1: A bamboo-ceramic solid waste-based core-shell hollow spherical filler, the filler is a spherical particle with a particle size of 3-8mm, and has a three-level composite structure of "shell-core-hollow" from the outside to the inside; wherein, the core is a hydrophilic bamboo-based porous carbon-ceramic sintered composite layer, the outer shell is a ceramic sintered layer, and the middle is a cavity; The preparation method of a bamboo-ceramic solid waste-based core-shell hollow spherical filler according to this embodiment includes the following steps: S1, Raw Material Processing Prepare bamboo-based solid waste and ceramic-based solid waste. Clean and remove impurities from the bamboo-based solid waste, dry it, and then pulverize it through a 100-200 mesh sieve to obtain bamboo-based powder. Clean and remove impurities from the ceramic-based solid waste, dry it, and then pulverize it through a 100-200 mesh sieve to obtain ceramic-based powder. Then, the bamboo-based powder was heated to 500℃ at a heating rate of 5℃ / min under a nitrogen atmosphere with a flow rate of 45mL / min, and held at that temperature for 1.5h for calcination and carbonization. The powder was then cooled to 25℃ in the furnace to obtain bamboo charcoal powder. The bamboo charcoal powder was then soaked in a 4.5% H2O2 solution and stirred at 23℃ for 2.2h. After filtration, it was washed with deionized water until neutral and then dried in an oven at 80℃ for 4h to obtain hydrophilic bamboo charcoal powder. Ceramic powder, binder, and dispersant were mixed with water in a mass ratio of 100:7:4:50 and ball-milled at 300 rpm for 2 hours. The viscosity of the mixture was measured using an NDJ-1 rotational viscometer at 25°C and 100 r / min to prepare a ceramic slurry with a viscosity of 650 mPa·s. The binder was starch and the dispersant was sodium carboxymethyl cellulose. S2, Preparation of core-shell structured raw material pellets Using naphthalene spheres with a diameter of 1.5 mm as templates, a small amount of ceramic slurry is first sprayed onto the template surface to moisten the surface of the volatile organic compounds spheres. Then, hydrophilic bamboo charcoal powder is coated onto the surface. This process is repeated by alternating between spraying a small amount of ceramic slurry and coating with hydrophilic bamboo charcoal powder. After each coating, the spheres are rolled and granulated to obtain a core with a hydrophilic bamboo-based porous carbon layer as the outermost layer. A layer of ceramic slurry is then sprayed onto the outermost layer, and the granulation process continues to roll and granulate to obtain a ceramic-based sintered outer shell, forming raw material spheres with a core-shell structure and a particle size of 3-8 mm. S3, Post-processing Raw material pellets with a core-shell structure were dried at 85℃ for 8 hours until the moisture content was 4.5%. Then, under nitrogen atmosphere protection, the temperature was increased to 1100℃ at a heating rate of 4℃ / min and held for 1.3 hours. After the heating was completed, the pellets were cooled to room temperature with the furnace to obtain bamboo ceramic solid waste-based core-shell hollow spherical fillers. Spherical fillers with a particle size of 4-6mm were screened, sealed in aluminum foil bags, and stored in a dry and light-proof environment. Bamboo-based solid waste is bamboo shavings, while ceramic-based solid waste is waste clay. In S2, the single spraying time of the ceramic slurry increases accordingly from 13 to 70 seconds as the particle size of the raw material balls increases. During the preparation of the core, the amount of hydrophilic bamboo charcoal powder used at one time is 0.7 g, and the spraying rate of the ceramic slurry is 200 μL / s. This satisfies the requirement that when the particle size of the raw material balls increases to about 3-4 mm, the single spraying time is controlled at 18 seconds; when the particle size increases to about 5-6 mm, the single spraying time is controlled at 30 seconds. During the preparation of the outer shell, i.e., when the particle size increases to about 7-8 mm, the spraying rate of the ceramic slurry is 200 μL / s, and the single spraying time is controlled at 60 seconds.
[0022] Example 2: Application of the bamboo-ceramic solid waste-based core-shell hollow spherical packing material prepared according to the preparation method of Example 1. The bamboo-ceramic solid waste-based core-shell hollow spherical packing material is used to treat antibiotic-containing wastewater in an anoxic biological filter. Configuration of anoxic biological filter: Construct an upflow or downflow anoxic biological filter (plexiglass columns, Φ×H=150mm×2500mm), with a total filling height of 1.8m and a filling rate of 65%; the filling material consists of bamboo-ceramic solid waste-based core-shell hollow spheres and particles with a diameter of 4-6mm and an effective specific surface area of 550m². 2 / m 3 The ordinary ceramsite was mixed in a volume ratio of 13:87. In application, the anoxic biological filter is started using the inoculation biofilm method. Activated sludge or compound denitrifying bacteria from the anoxic section of a pharmaceutical wastewater treatment plant are inoculated, and the filter is aerated (DO < 0.5 mg / L) for 24 hours. Afterward, continuous influent is introduced, with glucose added to achieve a concentration of 48 mg / L. Glucose serves as a co-metabolic carbon source. The influent flow rate is gradually increased to the target value (corresponding to HRT = 5 hours) over 12 hours. The biofilm formation period is ≤ 5 days. Microscopic examination reveals abundant biofilm growth on the packing surface and a well-structured flocculent structure. During operation, the dissolved oxygen in the anoxic biological filter is controlled at 0.4 mg / L and the pH at 7.5. Entering the stable operation phase, the influent water quality is as follows: total antibiotic concentration 65 μg / L, BOD5 / COD = 0.36; According to the hierarchical operation strategy The first-level scheme is activated: the core-shell hollow spherical packing material based on bamboo and ceramic solid waste accounts for 8% of the total packing volume, the hydraulic retention time is 5 hours, and the denitrification volumetric load is 0.4 kgN / (m³・d). The ratio of carbon source to filler is dynamically adjusted during operation: If the effluent nitrate nitrogen concentration is >15mg / L, then glucose carbon source should be added, and the dosage should be controlled to increase the influent COD by 75mg / L. If the effluent antibiotic concentration is greater than 10% of the influent antibiotic concentration, the proportion of bamboo ceramic filler should be increased by 4%, but the total proportion should not exceed 20%. If the effluent nitrate nitrogen concentration is >15mg / L and the effluent antibiotic concentration is >10% of the influent antibiotic concentration, then adjust the water in the order of first adding carbon source and then increasing the proportion of packing material. After the system has been running continuously and stably for 30 days, influent and effluent water samples were taken for monitoring. The results are as follows: Antibiotic removal efficiency: The removal rates of tetracycline and oxytetracycline were consistently maintained above 96%, with effluent concentrations below 2.5 μg / L; Denitrification efficiency: The average influent total nitrogen (TN) concentration was 92 mg / L, and the average effluent TN concentration was reduced to 9.8 mg / L, achieving a TN removal rate of 89.3%; Conventional pollutant removal efficiency: The average influent CODcr concentration was 285 mg / L, and the average effluent CODcr concentration remained consistently below 32 mg / L, achieving a removal rate of 88.8%; The average influent BOD5 concentration was 103 mg / L, and the average effluent BOD5 concentration remained consistently below 5.1 mg / L, achieving a removal rate of 95.0%. All conventional effluent indicators consistently met the Class A standard of the "Discharge Standard of Pollutants for Municipal Wastewater Treatment Plants" (GB18918-2002).
[0023] Example 3: Unlike Example 1, bamboo-based powder was heated to 400°C at a heating rate of 5°C / min under a nitrogen atmosphere with a flow rate of 40 mL / min, and carbonized for 1 hour to obtain bamboo charcoal powder.
[0024] Example 4: Unlike Example 1, bamboo-based powder was heated to 600°C at a heating rate of 5°C / min under a nitrogen atmosphere with a flow rate of 50 mL / min, and carbonized for 2 hours to obtain bamboo charcoal powder.
[0025] Example 5: Unlike Example 1, bamboo charcoal powder was soaked in a 4% H2O2 solution, stirred at 22°C for 2 hours, and dried to obtain hydrophilic bamboo charcoal powder.
[0026] Example 6: Unlike Example 1, bamboo charcoal powder was soaked in a 5% H2O2 solution, stirred at 25°C for 2.5 hours, and then dried to obtain hydrophilic bamboo charcoal powder.
[0027] Example 7: Unlike Example 1, ceramic powder, binder and dispersant were mixed with water in a mass ratio of 100:5:3:40 and ball-milled to prepare a ceramic slurry with a viscosity of 500 mPa·s. The viscosity of the slurry was measured using an NDJ-1 type rotational viscometer at 25°C and 100 r / min, and the viscosity of the slurry was 650 mPa·s.
[0028] Example 8: Unlike Example 1, ceramic powder, binder and dispersant were mixed with water in a mass ratio of 20:2:1:12 and ball-milled to prepare a ceramic slurry with a viscosity of 800 mPa·s. The viscosity of the slurry was measured using an NDJ-1 type rotational viscometer at 25°C and 100 r / min, and the viscosity of the slurry was 650 mPa·s.
[0029] Example 9: Unlike Example 1, in the process of preparing the core, the amount of hydrophilic bamboo charcoal powder used at one time is 0.2g, and the spraying rate of the ceramic slurry is 100μL / s. When the particle size of the raw material balls increases to about 3-4mm, the spraying time per time is controlled at 13s; when the particle size increases to about 5-6mm, the spraying time per time is controlled at 25s. In the process of preparing the outer shell, when the particle size increases to about 7-8mm, the spraying rate of the ceramic slurry is 100μL / s, and the spraying time per time is controlled at 50s.
[0030] Example 10: Unlike Example 1, in the process of preparing the core, the amount of hydrophilic bamboo charcoal powder used at one time was 1.2g, and the spraying rate of the ceramic slurry was 300μL / s. This met the requirements that when the particle size of the raw material balls increased to about 3-4mm, the single spraying time was controlled to be 20s; when the particle size increased to about 5-6mm, the single spraying time was controlled to be 40s. In the process of preparing the outer shell, that is, when the particle size increased to about 7-8mm, the spraying rate of the ceramic slurry was 300μL / s, and the single spraying time was controlled to be 70s.
[0031] Example 11: Unlike Example 1, the raw material balls with a core-shell structure were dried at 60°C for 4 hours until the moisture content was 5%. Then, under nitrogen atmosphere protection, the temperature was increased to 1050°C at a heating rate of 2°C / min and held for 0.5 hours to obtain bamboo ceramic solid waste-based core-shell hollow sphere filler.
[0032] Example 12: Unlike Example 1, the raw material balls with core-shell structure were dried at 105°C for 12 hours until the moisture content was 5%. Then, under nitrogen atmosphere protection, the temperature was raised to 1150°C at a heating rate of 5°C / min and held for 2 hours to obtain bamboo ceramic solid waste-based core-shell hollow sphere filler.
[0033] Example 13: Unlike Example 2, the total filling height of the packing is 1.5m and the filling rate is 60%.
[0034] Example 14: Unlike Example 2, the total filling height of the packing is 2.0m and the filling rate is 70%.
[0035] Example 15: Unlike Example 2, this example simulates the treatment of secondary biological treatment effluent from a chemical synthesis pharmaceutical plant. This wastewater is characterized by a moderate concentration of quinolone antibiotics (total concentration approximately 180 μg / L), extremely poor biodegradability (BOD5 / COD≈0.21), a low carbon-to-nitrogen ratio, and the presence of recalcitrant organic matter, making advanced treatment challenging. The purpose of this example is to verify the adaptability and treatment effect of this invention on recalcitrant wastewater with a low C / N ratio under a secondary operation scheme. By controlling the amount of ceramic slurry sprayed and the amount of carbon powder added, the final core-shell mass ratio was adjusted to 4:6 to appropriately enhance the mechanical strength of the filler shell; the measured compressive strength was 2.5 MPa, the specific surface area was 320 m² / g, and the porosity was 42%. Basic configuration of the filter bed: The addition ratio of bamboo ceramic packing is increased to 13% of the total volume of the packing; The inoculum was taken from aerobic sludge from a municipal wastewater treatment plant and pre-acclimated to anoxic conditions in the laboratory for one week using synthetic water (containing 10 mg / L norfloxacin). The biofilm formation process was the same as in Example 2, with a co-metabolic carbon source of a mixture of 45 mg / L glucose and 5 mg / L yeast extract. The biofilm formation period was extended to 6 days. Due to the poor biodegradability of the wastewater, the biofilm formation period was slightly prolonged, but the system eventually stabilized. Under graded operation control: Influent water quality: total concentration of quinolone antibiotics 178 μg / L, BOD5 / COD = 0.21. According to the "dual core indicators," since BOD5 / COD < 0.3, a graded operation scheme is applicable. The control parameters are as follows: HRT extended to 7 hours; DO concentration 0.3-0.5 mg / L; pH value 7.6-7.8; denitrification volumetric loading controlled at 0.25 kgN / (m³·d); Results and Effects: After the system stabilized: Antibiotic removal efficiency: The removal rates of norfloxacin and ciprofloxacin reached 90% and 87% respectively, and the effluent concentration was significantly reduced; Denitrification efficiency: Influent nitrate nitrogen (NO3) - The NO3- concentration in the effluent was 38 mg / L. - -N concentration remained stable below 6.5 mg / L, with a removal rate of 83%. For conventional pollutant removal: the average influent CODCr concentration was 158 mg / L, and the average effluent CODCr concentration decreased to 42 mg / L, achieving a removal rate of 73.4%. The average influent BOD5 concentration was 33 mg / L, and the average effluent BOD5 concentration remained stable at 6.8 mg / L, achieving a removal rate of 79.4%. Despite the poor biodegradability of the influent, the system effectively degraded organic matter through the synergistic effect of adsorption and biodegradation by the packing material, achieving Class A effluent standards.
[0036] Example 16: Unlike Example 2, this example simulates the treatment of high-concentration process flushing wastewater intermittently discharged from a pharmaceutical plant, characterized by high concentrations of antibiotics (mainly sulfonamides, >250 μg / L), high bioinhibition, and high organic matter concentration. The purpose of this example is to verify the effectiveness, stability, and rapid recovery capability of the present invention and its three-stage operating scheme in response to extreme shock loads. The filler was prepared in the same way as in Example 2. The actual performance of the finished product was as follows: particle size 4.0-6.0 mm, compressive strength 2.3 MPa, specific surface area 350 m² / g, porosity 45%, which meets the requirement of not breaking after a 1 m drop. Filter start-up and operation: Basic filter configuration: The filter system from Example 2, which has been operating stably, was used; Shock load test and operation control: The influent was switched to simulated shock wastewater (total sulfonamide antibiotics 285 μg / L. Rapid pre-test showed that after mixing this water sample with activated sludge for 30 minutes, the sludge settling ratio (SV30) decreased by 38%), and the three-level operation plan was activated. The total volume ratio of bamboo ceramic packing in the system was increased to 20% (maximum allowable value) in one go, the HRT was extended to 9 hours, the DO was strictly controlled at 0.1~0.3mg / L, and the denitrification volume load was reduced to 0.15kgN / (m³·d).
[0037] Dynamic adjustment: Monitoring was conducted 24 hours after the shock load was applied, and the effluent antibiotic concentration rose to 16% of the influent concentration. According to the dynamic adjustment rules described in the claim, the adjustment was immediately implemented: while keeping other parameters unchanged, the proportion of bamboo ceramic packing was further increased from 15% to 18% (achieved by directly adding packing to the top of the reactor).
[0038] Results and Effects: No large-scale biofilm shedding or system collapse occurred during the entire shock test. Antibiotic Removal Efficiency: Within 36 hours after dynamic adjustment, the effluent antibiotic concentration continuously decreased and eventually stabilized below 8% of the influent concentration (i.e., removal rate >92%). Nitrogen Removal Efficiency: The effluent NO3⁻-N concentration remained below 12 mg / L throughout the entire process. Conventional Pollutant Removal Efficiency and Stability: The shock influent CODCr reached 520 mg / L, and BOD5 was 155 mg / L. In the initial stage of the shock (within 24 hours), effluent CODCr and BOD5 briefly increased, but the treatment efficiency quickly recovered with system adjustments (increasing the proportion of bamboo-ceramic packing). After stabilization, the effluent CODCr stabilized below 50 mg / L, and BOD5 stabilized below 10 mg / L, successfully withstanding the shock load and demonstrating the system's strong buffering and recovery capabilities, with the effluent consistently meeting standards.
[0039] Experimental Example 1: The description of this experimental example is based on the scheme described in Example 2, and aims to illustrate the practical application effect of the present invention.
[0040] Table 1. Comparison of the application effects of bamboo ceramic solid waste-based core-shell hollow sphere packing materials in Examples 2, 15-16
[0041] Conclusion: As shown in Table 1, the packing material prepared in this application exhibits good comprehensive treatment efficiency under low-load stable conditions, particularly in its ability to simultaneously perform deep denitrification, antibiotic removal, and degradation of conventional organic matter. This is because the operation strategy is divided into three levels based on the dual core indicators of "total antibiotic concentration" and "BOD5 / COD" in the influent, which has the following advantages: First, it can adapt to water quality fluctuations. Low load (level 1) uses 5-10% bamboo-ceramic packing material and 4-6 hRT to save costs, while high load (level 3) uses 15-20% bamboo-ceramic packing material and 8-10 hRT to ensure compliance, avoiding over-treatment or under-treatment. Second, it ensures the synergy of "adsorption-degradation-denitrification," with each level matching the suitable environment for denitrifying bacteria (DO 0.2-0.5 mg / L, pH 7.0-8.0) to ensure functional stability. Third, it enhances shock resistance. For example, the level 3 scheme can withstand antibiotic shocks of >200 μg / L, and the system operates continuously without fluctuations and recovers quickly after shocks, ensuring stable operation.
[0042] Experiment Example 2: Investigating the effect of the preparation method of bamboo-ceramic solid waste-based core-shell hollow spherical packing material on the treatment effect of antibiotic-containing wastewater.
[0043] Comparative Example 1: Unlike Example 1, bamboo-based powder was heated to 500°C at a heating rate of 5°C / min in an air atmosphere with a flow rate of 45 mL / min, and then calcined and carbonized for 1.5 h.
[0044] Comparative Example 2: Unlike Example 1, it lacks the modification step of soaking bamboo charcoal powder in a 4.5% H2O2 solution and stirring at 23°C for 2.2 hours.
[0045] Comparative Example 3: Unlike Example 1, the ceramic slurry granulation process was replaced with a tableting process.
[0046] Comparative Example 4: Unlike Example 1, the post-processing stage does not use gradient sintering, but is directly dried at a temperature of 1100°C.
[0047] Table 2 Comparison of packing material performance and treatment effect on antibiotic-containing wastewater obtained from Examples 1, 3-14 and Comparative Examples 1-4
[0048] Conclusion: Based on the comparison of Examples 1 / 2, Examples 3-4, and Control Example 1 in the table, it can be concluded that replacing nitrogen with air as the carbonization gas has an adverse effect on the performance of the packing material and the treatment effect on antibiotic-containing wastewater. This is because air oxidation causes the pores of the bamboo-based powder to collapse, resulting in a specific surface area of <150m² / g (only 43% of that in Example 1), a porosity of 25% (a decrease of 44%), a compressive strength of 1.2MPa (a decrease of 48%), and uneven particle size. Furthermore, due to insufficient antibiotic adsorption sites, the tetracycline removal rate is <60% (a decrease of 37%), there is less denitrifying bacteria attachment, the TN removal rate is <55% (a decrease of 38%), and the biofilm formation period exceeds 10 days (doubles).
[0049] The comparison between Examples 1 / 2, Examples 5-6, and Control Example 2 in the table shows that the lack of the modification step of soaking bamboo charcoal powder in a 4.5% H2O2 solution and stirring at 23°C for 2.2 hours has an adverse effect on the performance of the packing material and the treatment effect on antibiotic-containing wastewater. This is because the unmodified bamboo charcoal has no carboxyl / hydroxyl groups on its surface, resulting in poor hydrophilicity and a reduced specific surface area of 280 m² / g (a decrease of 20%). At the same time, the treatment efficiency for antibiotic-containing wastewater is also greatly reduced due to the difficulty of microbial adhesion, specifically manifested in a biofilm formation period of 9 days (an increase of 80%), a TN removal rate of 72.4% (a decrease of 19%), and a tetracycline removal rate of 82% (a decrease of 15%).
[0050] The comparison of Examples 1 / 2, Examples 9-10 and Comparative Example 3 in the table shows that replacing the granulation process with the tableting process will have an adverse effect on the performance of the packing material and the treatment effect on antibiotic-containing wastewater. This is because the packing material lacks a core-shell structure and has a loose outer shell, which reduces the performance of the packing material. Specifically, the compressive strength is reduced to 0.8 MPa (down 65%), the porosity is reduced to 30% (down 33%), and it is easily broken. At the same time, the lack of a core-shell structure blocks the mass transfer channels, which results in a weakened treatment effect on antibiotic-containing wastewater, with tetracycline removal rate <55% (down 43%) and TN removal rate <60% (down 33%).
[0051] As can be seen from the comparison of Examples 1 / 2, Examples 11-12 and Comparative Example 4 in the table, the failure to use gradient sintering in the post-treatment stage and the direct drying at 1100℃ will have adverse effects on the performance of the packing and the treatment effect on antibiotic-containing wastewater. This is because direct sintering at high temperature will result in the outer shell lacking a dense structure, with a compressive strength of 0.6MPa (reduced by 74%) and a porosity of 20% (reduced by 56%). Due to the reduced performance of the packing itself, antibiotics cannot be enriched in the core, resulting in a removal rate of <45% (reduced by 53%); the anoxic microenvironment is destroyed, with a TN removal rate of <40% (reduced by 55%) and no stable biofilm.
[0052] In summary, the bamboo-ceramic solid waste-based core-shell hollow spherical packing material prepared by the method of this application possesses the characteristics of full resource utilization of solid waste, synergistic three-level structure, strong mechanical properties, high treatment efficiency, and impact resistance and stability, which represents a significant improvement over existing technologies.
Claims
1. A method for preparing a bamboo-ceramic solid waste-based core-shell hollow spherical filler, characterized in that, The filler is a spherical particle with a particle size of 3-8mm, and has a three-level composite structure of "shell-core-hollow" from the outside to the inside; wherein, the core is a hydrophilic bamboo-based porous carbon-ceramic sintered composite layer, the outer shell is a ceramic-based sintered layer, and the middle is a cavity; The method for preparing the filler includes the following steps: S1, Raw Material Processing Prepare bamboo-based solid waste and ceramic-based solid waste separately. Clean and remove impurities from the bamboo-based solid waste, dry it, and then pulverize it through a 100-200 mesh sieve to obtain bamboo-based powder. Clean and remove impurities from the ceramic-based solid waste, dry it, and then pulverize it through a 100-200 mesh sieve to obtain ceramic-based powder. Then, the bamboo-based powder is carbonized under an inert atmosphere to obtain bamboo charcoal powder. The bamboo charcoal powder is then soaked in a 4-5% H2O2 solution and stirred at 22-25℃ for 2-2.5 hours. After drying, hydrophilic bamboo charcoal powder is obtained. Ceramic base powder, binder and dispersant are mixed with water in a mass ratio of 100:5-10:3-5:40-60 and ball-milled to prepare a ceramic slurry with a viscosity of 500-800 mPa·s. S2, Preparation of core-shell structured raw material pellets Using volatile organic compound spheres as templates, a small amount of ceramic slurry is first sprayed onto the template surface to moisten the surface of the volatile organic compound spheres. Then, hydrophilic bamboo charcoal powder is coated onto the surface. This process is repeated alternately with spraying a small amount of ceramic slurry and coating with hydrophilic bamboo charcoal powder. After each coating, the spheres are rolled and granulated to obtain a core with a hydrophilic bamboo-based porous carbon layer as the outermost layer. A layer of ceramic slurry is then sprayed onto the outermost layer, and the granulation process continues to produce a ceramic-based sintered outer shell, forming raw material spheres with a core-shell structure and a particle size of 3-8 mm. In S2, the volatile organic compound spheres are naphthalene spheres with a diameter of 1-2 mm. The single spraying time of the ceramic slurry increases accordingly from 13 to 70 s as the particle size of the raw material spheres increases. During the preparation of the core, the amount of hydrophilic bamboo charcoal powder used per application is 0.2-1.2 g, and the spraying rate of the ceramic slurry is 100-300 μL / s. This ensures that when the particle size of the raw material spheres increases to 3-4 mm, the single spraying time is controlled to be 13-20 s; when the particle size increases to 5-6 mm, the single spraying time is controlled to be 25-40 s. During the preparation of the outer shell, i.e., when the particle size increases to 7-8 mm, the spraying rate of the ceramic slurry is 100-300 μL / s, and the single spraying time is controlled to be 50-70 s. S3, Post-processing The raw material balls with a core-shell structure are dried by forced air at 60-105℃ for 4-12 hours until the moisture content is <5%. Then, under nitrogen atmosphere protection, the temperature is raised to 1050-1150℃ at a heating rate of 2-5℃ / min and held for 0.5-2 hours to obtain the core-shell hollow spherical filler based on bamboo ceramic solid waste. The filler with a particle size of 3-8mm is screened and sealed in packaging.
2. The preparation method of the bamboo-ceramic solid waste-based core-shell hollow spherical filler as described in claim 1, characterized in that, The bamboo-based solid waste is bamboo shavings or bamboo powder, and the ceramic-based solid waste is waste clay or waste porcelain powder.
3. The preparation method of the bamboo-ceramic solid waste-based core-shell hollow spherical filler as described in claim 1, characterized in that, In S1, the inert atmosphere is nitrogen, with a flow rate of 40-50 mL / min, and the carbonization conditions are: heating to 400-600℃ at a heating rate of 5℃ / min and holding at that temperature for 1-2 hours.
4. The preparation method of the bamboo-ceramic solid waste-based core-shell hollow spherical filler as described in claim 1, characterized in that, The binder is starch, and the dispersant is sodium carboxymethyl cellulose.
5. The application of the bamboo-ceramic solid waste-based core-shell hollow spherical filler prepared by the preparation method according to any one of claims 1 to 4, characterized in that, Bamboo-ceramic solid waste-based core-shell hollow spherical packing material was used to treat antibiotic-containing wastewater in anoxic biological filters. Configuration of anoxic biological filter: Construct an upflow or downflow anoxic biological filter with a total filling height of 1.5-2.0m and a filling rate of 60-70%; the filling material consists of bamboo-ceramic solid waste-based core-shell hollow spheres with a particle size of 2-6mm and an effective specific surface area of 500-600m². 2 / m 3 The ordinary ceramsite is composed of a compound with a volume ratio of 5-20:80-95; When applying the solution, start the anoxic biological filter, inoculate it with activated sludge or compound denitrifying bacteria from the anoxic section of the pharmaceutical wastewater treatment plant, aerate for 24 hours, then add glucose to achieve a concentration of 45-50 mg / L in the water. Gradually increase the influent flow rate to the target value within 12 hours. During operation, control the dissolved oxygen in the anoxic biological filter to be 0.2-0.5 mg / L and the pH to be 7.0-8.
0. The target values are obtained by dividing the effective volume of the filter by the target HRT.
6. The application of the bamboo-ceramic solid waste-based core-shell hollow spherical filler as described in claim 5, characterized in that, The application is based on two core indicators of influent: "total antibiotic concentration" and "BOD5 / COD," and adopts a tiered operation strategy. The tiered operation method is as follows: When the total antibiotic concentration is ≤100 μg / L and BOD5 / COD ≥0.3, The primary scheme is implemented as follows: Bamboo-ceramic solid waste-based core-shell hollow spherical packing material accounts for 5-10% of the total packing volume; the hydraulic retention time is 4-6 hours; and the denitrification volumetric loading is 0.3-0.5 kgN / (m³). 3 ·d); When the total antibiotic concentration is 100-200 μg / L or BOD5 / COD < 0.3, The secondary scheme is activated: bamboo-ceramic solid waste-based core-shell hollow spherical packing accounts for 10-15% of the total packing volume, the hydraulic retention time is 6-8 hours, and the denitrification volumetric loading is 0.2-0.4 kgN / (m³). 3 ·d); When the total concentration of antibiotics is >200 μg / L or the wastewater has bioinhibitory properties... The three-stage scheme is implemented: bamboo-ceramic solid waste-based core-shell hollow spherical packing accounts for 15-20% of the total packing volume; the hydraulic retention time is 8-10 hours; and the denitrification volumetric loading is 0.1-0.3 kgN / (m³). 3 ·d); The method for determining the biological inhibition is as follows: after the influent sample is mixed with activated sludge for 20-30 minutes, the sludge settling ratio decreases by more than 20%.
7. The application of the bamboo-ceramic solid waste-based core-shell hollow spherical filler as described in claim 6, characterized in that, The ratio of carbon source to filler is dynamically adjusted during operation: If the effluent nitrate nitrogen concentration is >15mg / L, then glucose carbon source should be added, and the dosage should be controlled to increase the influent COD by 50-100mg / L. If the effluent antibiotic concentration is greater than 10% of the influent antibiotic concentration, the proportion of bamboo ceramic filler should be increased by 3-5%, but the total proportion should not exceed 20%. If the effluent nitrate nitrogen concentration is >15mg / L and the effluent antibiotic concentration is >10% of the influent antibiotic concentration, then adjust the water according to the order of first adding carbon source and then increasing the proportion of packing material.
Citation Information
Patent Citations
Bamboo charcoal-based microelectrolysis porous ceramsite filler and preparing method thereof
CN104003483A
Biological treatment method for high-concentration ammonia nitrogen wastewater from chemical industry
CN105906057A
Sludge carbon biological filler with core-shell structure as well as preparation method and application of sludge carbon biological filler
CN115121224A
Preparation method and application of curable bacterial carrier bed
CN120504396A